2016
DOI: 10.1007/s12630-016-0780-1
|View full text |Cite
|
Sign up to set email alerts
|

The impaired anesthesiologist: what you should know about substance abuse

Abstract: Due to the considerable morbidity and mortality associated with the abuse of anesthetic agents as well as the continuous increase in the rate of substance abuse by anesthesia providers, it is essential for anesthesia care providers to become familiar with the presenting signs and symptoms of substance abuse and impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
(100 reference statements)
0
22
0
1
Order By: Relevance
“…Nous devons comprendre les troubles d'addiction de substance. 25,26 Nous devons apporter aux personnes à risque le soutien social, médical, psychiatrique et spirituel dont ils ont besoin pour aborder les causes profondes qui les exposent au risque d'utilisation des opioïdes. Nous devons traiter le trouble d'abus des opioïdes comme une maladie, ce qui signifie de fournir les moyens financiers pour la recherche et le traitement comme nous le faisons pour toutes les autres menaces significatives sur la santé du public (par exemple, le cancer, les maladies cardiaques, le diabète).…”
Section: Carfentanil: Une Arme De Destruction Massiveunclassified
See 1 more Smart Citation
“…Nous devons comprendre les troubles d'addiction de substance. 25,26 Nous devons apporter aux personnes à risque le soutien social, médical, psychiatrique et spirituel dont ils ont besoin pour aborder les causes profondes qui les exposent au risque d'utilisation des opioïdes. Nous devons traiter le trouble d'abus des opioïdes comme une maladie, ce qui signifie de fournir les moyens financiers pour la recherche et le traitement comme nous le faisons pour toutes les autres menaces significatives sur la santé du public (par exemple, le cancer, les maladies cardiaques, le diabète).…”
Section: Carfentanil: Une Arme De Destruction Massiveunclassified
“…We must understand the causes of substance use disorder. 25,26 We must provide individuals at risk with the social, medical, psychiatric, and spiritual support to address the root causes that place them at risk of opioid use. We need to treat opioid abuse disorder as a disease, which means providing the research and therapeutic investment we make in every other significant threat to public health (i.e., cancer, heart disease, diabetes).…”
mentioning
confidence: 99%
“…Another study found that approximately 15% of these practitioners will abuse substances at some point in their careers (Valdes, 2014). Samuelson and Bryson (2016) found that anaesthesia providers are more likely to abuse drugs than alcohol. The abuse of opioids, ketamine, propofol (intravenous anaesthetic that potentiates the inhibitory effects of GABA), benzodiazepines and inhaled anaesthetic agents (volatile anaesthetics such as enflurane, isoflurane and halothane) is increasing in prevalence among anaesthesia providers (Bryson, 2018).…”
Section: Prevalencementioning
confidence: 99%
“…This sense of invulnerability stems from the task of manipulating patient vital signs and neurological functions while handling highly addictive anaesthetics and opioids every day. Many anaesthesia providers feel they will not fall prey to addiction due to their knowledge of pharmacology (Samuelson and Bryson, 2016). The workplace is often the last place where substance abuse is recognised, while family and friends are often the first people to suspect addiction because they know the individual so well (Bryson and Silverstein, 2008; Wearing Masks, 2006).…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation